Nuclear factor kappa-B contributes to cigarette smoke tolerance in pancreatic ductal adenocarcinoma through cysteine metabolism - Venugopal Gunda (Elsevier, 2021)
Background: Retrospective studies revealed that cigarette smoking enhances risk of incidence and worsens prognosis in pancreatic cancer (PC) patients. Poor prognosis in smoker cohort of PC patients indicates prevalence of cigarette smoke stimulated survival mechanisms yet to be explored in PC. In this study, cigarette smoke induced metabolic pathways were explored and targeted in PC. Methods: Human pancreatic ductal adenocarcinoma cell (PDAC) lines, genetically engineered mice models (GEMMs), mass spectrometry based heavy isotope-based metabolite analysis, cytotoxicity assays and Nuclear factor kappa-B (NF-kB) targeting were utilized in this study. Cigarette smoke extract (CSE) was prepared fresh each day by bubbling cell culture media with the smoke emitted from 85 mm, filtered, Code 1R6F reference cigarettes and used for in vitro procedures. High dose cigarette smoke exposure of GEMMs was achieved by daily exposure of animals to similar cigarettes, 6 h/day for a total period of 180 days. Findings: We observed that PDAC cells upregulate glutathione anabolism through cysteine uptake and glutamate cysteine ligase (GCLM), supporting survival, upon CSE exposure. In vivo, cigarette smoke exposure leads to concomitant upregulation of GCLM and activated NF-kB in the PDAC consistent with in vitro, in CSE-exposed PDAC. Finally, either inhibition of NF-kB or depletion of cysteine impaired PDAC cell survival in cigarette smoke exposed conditions through suppression of glutathione and ROS enhancement, reverted by glutathione supplementation. Interpretation: Our findings demonstrate scope for targeting smoke induced, NF-kB mediated, cysteine and glutathione metabolism for improving the survival of smoke addicted PDAC.